Why Do More People Marry in Winter? An Exploration of Seasonal Preferences - Hassan Jubair; Mithela Mehenaz (Penerbit Hellow Pustaka, 2025)
This study examines the seasonal preference for winter weddings, analyzing cultural, economic, and environmental factors that influence this trend globally. Focusing on regions such as Bangladesh and India, where winter weddings are predominant, the research highlights how favorable climatic conditions, alignment with cultural and religious traditions, and economic advantages drive this preference. Winter offers mild weather, suitable for outdoor events, and coincides with holidays and post-harvest periods, facilitating extended celebrations and family gatherings. Additionally, reduced costs for venues and the availability of seasonal produce contribute to the practicality and appeal of winter weddings. Conversely, in regions with harsh winters, such as Northern Europe and North America, summer and autumn are preferred due to more accommodating weather for outdoor ceremonies and reduced logistical challenges. The study acknowledges the obstacles of winter weddings, including adverse weather, limited daylight, and holiday scheduling conflicts, which can complicate planning. Despite these challenges, winter weddings remain a favored choice in many regions, reflecting a confluence of cultural practices, environmental factors, and economic considerations. This research underscores the intricate relationship between seasonal preferences, local traditions, and practical constraints in shaping global marriage patterns.